Random amplified polymorphic DNA (RAPD) analysis of Pasteurella multocida and Manheimia haemolytica strains isolated from cattle, sheep and goats - Ozbey, G; Kilic, A; Ertas, HB; Muz, A (Czech Academy Agricultural Sciences, 2004)
In this study, 30, 15 and 1 strains of Pasteurella multocida and 9, 8 and 6 strains of Mannheimia haemolytica from cattle, sheep and goats isolated in Elazig province located in the East of Turkey, respectively were typed by random amplified polymorphic DNA (RAPD) assay using a random primer (OPA-11). By RAPD assay, two and three distinct band profiles were obtained in the examination of P. multocida isolates from cattle and sheep, respectively. However, M. haemolytica isolates from cattle, sheep and goats showed only one profile and these. strains were not discriminated by RAPD. This study showed that little genetic heterogeneity exists among P. multocida and M. haemolytica isolates from lungs of cattle, sheep and goats.
Keywords: Pasteurella multocida; Mannheimia haemolytica; random amplified polymorphic DNA; cattle; sheep and goats; typing